# Trigonometry?

Prove that,

(Cosec A + Cot A)(1-Cos A) -(Sec A + Tan A)(1 - Sin A) = (Cosec A - Sec A)[2 - (1 - Cos A)(1- Sin A)]

(Cosec A + Cot A)(1-Cos A) -(Sec A + Tan A)(1 - Sin A) = (Cosec A - Sec A)[2 - (1 - Cos A)(1- Sin A)]

Update:
Prove that,

(Cosec A + Cot A)(1-Sin A) -(Sec A + Tan A)(1 - Cos A) = (Cosec A - Sec A)[2 - (1 - Cos A)(1- Sin A)]

(Cosec A + Cot A)(1-Sin A) -(Sec A + Tan A)(1 - Cos A) = (Cosec A - Sec A)[2 - (1 - Cos A)(1- Sin A)]

Follow

5 answers
5

Are you sure you want to delete this answer?